2017
DOI: 10.1001/jamainternmed.2017.0918
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Life Expectancy Among US Counties, 1980 to 2014

Abstract: IMPORTANCEExamining life expectancy by county allows for tracking geographic disparities over time and assessing factors related to these disparities. This information is potentially useful for policy makers, clinicians, and researchers seeking to reduce disparities and increase longevity.OBJECTIVE To estimate annual life tables by county from 1980 to 2014; describe trends in geographic inequalities in life expectancy and age-specific risk of death; and assess the proportion of variation in life expectancy exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
254
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 345 publications
(272 citation statements)
references
References 17 publications
13
254
3
2
Order By: Relevance
“…If health equity is siloed in a separate office, chronic disease practitioners may not identify it as a primary area of their work or may not be collaborating with that office. (911) This is likely compounded by public health departments that are often organized into separate program areas that address specific diseases or risk factors and that are not well connected (often due to how funding is allocated at federal and state levels). It is also possible that the 9% of respondents who identify health equity as one of several work areas may be conceptualizing health equity as embedded in their primary areas of work, rather than as a specific area of focus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If health equity is siloed in a separate office, chronic disease practitioners may not identify it as a primary area of their work or may not be collaborating with that office. (911) This is likely compounded by public health departments that are often organized into separate program areas that address specific diseases or risk factors and that are not well connected (often due to how funding is allocated at federal and state levels). It is also possible that the 9% of respondents who identify health equity as one of several work areas may be conceptualizing health equity as embedded in their primary areas of work, rather than as a specific area of focus.…”
Section: Discussionmentioning
confidence: 99%
“…(10) In 2017, Dwyer-Lindgren and colleagues found that the association between life expectancy and socioeconomic and race/ethnicity factors was largely mediated by behavioral and metabolic risk factors such as obesity, physical activity, hypertension, and diabetes. (11) These are the domains of chronic disease prevention and control. (12) Consequently, state-level chronic disease practitioners are uniquely situated to not only bear witness to health inequities but also intervene upon them.…”
Section: Introductionmentioning
confidence: 99%
“…42 It is possible that when immigration to the United States leveled off, immigrants stopped contributing to life expectancy gains and that this drove recent declines in overall life expectancy in the United States. 14 The migration story is supported by a relatively strong correlation between mortality and in-migration trends and the fact that areas without major urban centers that attract healthy international migrants have experienced a leveling off in life expectancy over the past decade. 43 …”
Section: Alternative Storiesmentioning
confidence: 99%
“…Although mortality increases among those with declining socioeconomic mobility, particularly in Southern “stroke belt” counties and among White women, had been previously noted, 14 Case and Deaton provided a narrative with media resonance. They termed this excess mortality “deaths of despair,” on the basis of their finding that mortality increases were largely driven by suicide, cirrhosis of the liver, and fatal opioid-related overdoses— causes that suggest victims are likely to be suffering from psychological distress 16,17 .…”
mentioning
confidence: 98%
See 1 more Smart Citation